Menstrual disorders and associated factors among rural and tribal adolescent girls in India: A systematic review and meta-analysis - Chatterjee, Rashni; Chakrabarty, Suman (Anthropological Review, 2024)
After attaining menarche adolescents, due to shyness and fear, often refuse to seek medical treatment. Simultaneously they began to face menstrual disorders. The present review aimed to estimate the overall menstrual disorders and associated factors among adolescent girls in rural and tribal areas in India as well as to summarize the most recent research findings on the pooled prevalence of menstrual disorders. The study design was developed applying the PRISMA checklist-2020. The whole protocol was registered on PROSPERO (Registration ID: CRD42024385046). Articles (English language) related to menstrual irregularities among 10 to 19-year-old adolescent girls in India were collected based on inclusion and exclusion criteria from 2000 to 2023 followed by selected keywords. The quality assessment of the present study was evaluated using the CASP (Critical Appraisal Skills Programme) checklist. Meta-analysis was conducted by using MedCalc software version 22.0. Publication bias was checked using Egger’s test. A total of 61 studies (47 from rural and 14 from tribal areas) in India have been evaluated. The random effect model showed an overall prevalence of dysmenorrhea, irregular menstruation, PMS, oligomenorrhea, polymenorrhea and menorrhagia in both areas was 54.96% (95% CI: 47.93 to 61.85), 26.21% (95% CI: 20.73 to 32.09), 47.49% (95% CI: 31.44 to 63.81), 13.88% (95% CI: 8.98 to 19.65),7.85% (95% CI: 2.30 to 16.31), 16.83% (95% CI: 10.04 to 24.96) respectively. Among these, dysmenorrhea, irregular menstruation, and PMS were found to be the most predominant in both areas. Lack of physical activities, dietary habits, BMI, socioeconomic factors, and socio-cultural taboos were found to have a strong association with menstrual irregularities. Prior and after attaining menarche, proper guidance on every aspect of menstruation should be urgently arranged in schools and at home to get rid of fear and anxiety, so that adolescent girls can cope with menstrual-related issues. Health camps should be organized in both areas to allow an easy access.